COMPREHENSIVE SEXUALITY EDUCATION PADA SISWA SMP DI KOTA KEDIRI - Alita Dewi Percunda (Adiba Aisha Amira, 2023)
Background: Adolescents are in a development process where changes occur both physically and psychologically. Most teenagers experience various problems during puberty. Lack of knowledge about the changes they are experiencing makes teenagers vulnerable to falling into risky behavior such as unhealthy relationships, sexual violence, and smoking, alcohol and drug abuse. Method: Education is provided using the lecture method in large classes followed by interactive discussions. Results: The activity was attended by 76 public junior high school students in Kediri City where from the results of the questionnaire it was found that 21 people (27.6%) had never received similar material; as many as 43 people (56.6%) had experienced problems during puberty, both physical, psychological and emotional; as many as 18 people (23.7%) had been involved in an unhealthy relationship; as many as 5 people (6.6%) had experienced sexual violence; and 10 people (13.2%) had ever smoked or used drugs or alcohol. Conclusion: CSE as a structured sexuality education guide is very good for implementation in sexual education for teenagers. With sufficient knowledge, it is hoped that teenagers can avoid risky behavior.